A rare case of depressed skull fractures at the anterior cranial fossa associated with communicating hydrocephalus resulting a progressive vision loss - Ahmad Faried, MD., PhD; Christian B. Kurniawan, MD; Danny Halim, MD., PhD; Muhammad Z. Arifin, MD., PhD (Interdisciplinary Neurosurgery, 2019)
Although an open depressed skull fractures at the anterior cranial fossa is relatively common, comorbidity with a progressive vision loss at initial presentation, with acute communicating hydrocephalus is rare. Here we report a rare case of a progressive vision loss presented with communicating hydrocephalus following open depressed skull fractures at a mid-frontobasal. Fragments of skull were extracted and the dural tear was repaired. Within the first post-operative day, the patient already gained full consciousness and his headache was completely resolved. Unfortunately, the ophthalmologic examinations revealed his vision remains impaired. We discussed the pathological mechanisms of a progressive vision loss and acute communicating hydrocephalus in a patient who was diagnosed with traumatic open depressed skull fracture at a mid-frontobasal, with focus on surgical management of this intriguing case. This case makes a strong argument for an early neurosurgical intervention in frontobasal fractures. Keywords: Open depressed skull fractures at a mid-frontobasal, A progressive vision loss, Acute communicating hydrocephalus